APPLICATION OF SEISMIC DILATOMETER FOR CEMENTATION ANALYSIS IN RESIDUAL GNEISS SOIL - Silva, Fabio (2021)
Residual soils have different properties and behavior from sedimentary soils. Aspects related to the processes of origin and formation directly impact these geotechnical particularities. One of the characteristic properties of this material is cementation. Cementation is an additional resistance that occurs in the solid skeleton due to weathering actions on these materials. In a residual soil profile, different cementation levels occur between the grains, these differences are due to different types of matrix rock, decomposition mechanisms involved in the process and anthropic actions. This article evaluated changes in the degree of cementation in residual soil horizons using the Marchetti Seismic Dilatometer (SDMT). The research was carried out in a residual gneiss soil in the State of Santa Catarina. The evaluation of the cementation degree was based on the relationships obtained with the Go (shear modulus with small strain) and other field geotechnical indices. The results show that the interpretation of the correlations from the results obtained by the SPT (Standardized Penetration Test), CPT (Cone Penetration Test) and SDMT tests allow the identification of layer boundaries with different degrees of cementation in residual gneiss soils. . In the present work, the limits between the saprolitic and the lateritic layers were identified and, finally, it was concluded that the studied residual soil presents a low level of cementation between the particles.